Development of Bahasa Malaysia reflux symptom index (M-RSI) - Mohammad, Nik Mohd Yunus (2015)
Introduction : Reflux Symptom Index (RSI), is a nine-item self-administer questionnaire, functioned to help clinician to assess the relative degree of Laryngopharyngeal Reflux (LPR) symptoms during initial evaluation and outcome after treatment. Objective : The purpose of this study was to develop a Malay version of the RSI (M-RSI) and to evaluate its validity, concistency and reliability in normal Malaysia population with suspected LPR. Materials and methods : This is a prospective study involving a total of 84 patients presenting to otorhinology and head and neck (ORL-HNS) clinic. It was carried out at Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan. The developed Malaysian RSI (M-RSI) was administered to 50 patients with suspected LPR. Internal consistency and test-retest reliability were evaluated. Then, two group which consists of 17 patients with LPR and other 17 participants from control group were recruited to undergo the M-RSI questionnaire answering session, laryngeal examination and insertion of the 24 hours ambulatory pH monitoring. This is to test the validity of the M-RSI questionnaire by comparing with other tools for diagnosis of LPR including reflux finding score (RFS) by laryngeal examination and oropharnygeal pH monitoring. Results : The Malaysian M-RSI showed satisfactory internal consistency (Cronbach’s α = 0.60). Test-retest reliability was assessed using intraclass correlation coefficient (ICC). Intraclass Correlation Coefficient is 0.727 which is a good correlation between pre and post assessment. Spearman Rank correlation coefficient is applied to determine the correlation between the total M-RSI with total RFS, Ryan score upright and Ryan score supine. Significant correlation is demonstrated between total M-RSI and total RFS (r = 0.80, p<0.001). Conclusion: This study shows that Malaysian M-RSI is easily administered, highly reproducible and demonstrates good clinical validity. It is a valid tool for self-assessment of LPR that can be used by Malaysian population. Results : The Malaysian M-RSI showed satisfactory internal consistency (Cronbach’s α = 0.60). Test-retest reliability was assessed using intraclass correlation coefficient (ICC). Intraclass Correlation Coefficient is 0.727 which is a good correlation between pre and post assessment. Spearman Rank correlation coefficient is applied to determine the correlation between the total M-RSI with total RFS, Ryan score upright and Ryan score supine. Significant correlation is demonstrated between total M-RSI and total RFS (r = 0.80, p<0.001). Conclusion: This study shows that Malaysian M-RSI is easily administered, highly reproducible and demonstrates good clinical validity. It is a valid tool for self-assessment of LPR that can be used by Malaysian population.